Pemanfaatan Media Pembelajaran Berbasis iSpring Suite dalam Implementasi Kurikulum Merdeka di Siak: Utilization of iSpring Suite-Based Learning Media in the Implementation of the Independent Curriculum in Siak - Dipuja, Diah Anugrah; Yustina, Yustina; Zulfarina, Zulfarina; Nursal, Nursal; Darmadi, Darmadi (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
The Independent Curriculum is a framework established and implemented since the 2022/2023 academic year through the Decree of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 56/M/2022 concerning Guidelines for Curriculum Implementation. Implementing the Independent Curriculum significantly affects various aspects, especially selecting appropriate learning media. Based on the results of interviews and findings from field observations, many teachers have not made maximum use of existing technology in the learning process. Creative teachers need to develop interesting learning media for students because the independent curriculum is closely related to innovation. This community service activity aims to effectively train teachers at SMPN 1 Mempura, Siak Regency, to implement media-based learning according to the Independent Curriculum. The methods used in this service include socialization and guidance in designing and utilizing iSpring Suite media. The process consists of five stages: analysis, preparation, implementation, mentoring, and evaluation. The participants included 15 teachers at SMPN 1 Mempura, Siak Regency. The output of this activity was assessed through improvements in pretest and posttest results, as well as satisfaction surveys. The findings showed that 1) participants' knowledge increased by 39%, with an average pretest score of 61 and an average posttest score of 85, and 2) the results of the satisfaction survey showed that 93% of participants gave a positive response by categorizing their responses as very good.